2003
DOI: 10.1557/jmr.2003.0291
|View full text |Cite
|
Sign up to set email alerts
|

Semi-inverse method for predicting stress–strain relationship from cone indentations

Abstract: A method for determining the stress–strain relationship of a material from hardness values H obtained from cone indentation tests with various apical angles is presented. The materials studied were assumed to exhibit power-law hardening. As a result, the properties of importance are the Young's modulus E, yield strength Y, and the work-hardening exponent n. Previous work [W.C. Oliver and G.M. Pharr, J. Mater. Res. 7, 1564 (1992)] showed that E can be determined from initial force–displacement data collected wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…They suggested that the number of the indenters with different apex angles should equal the number of unknown constants in the constitutive model. Several variations of the multiple indenter approach using conical or pyramidal indenters have also appeared in the literature [174][175][176].…”
Section: Probing Stress-strain Relationshipsmentioning
confidence: 99%
“…They suggested that the number of the indenters with different apex angles should equal the number of unknown constants in the constitutive model. Several variations of the multiple indenter approach using conical or pyramidal indenters have also appeared in the literature [174][175][176].…”
Section: Probing Stress-strain Relationshipsmentioning
confidence: 99%
“…The dual indentation strategy we develop is of the same vain as other multiple indenter approaches recently proposed for elasto-plastic cohesive materials (with or without strain hardening) using conical or pyramidal indenters (Futakawa et al, 2001;Bucaille et al, 2003;Chollacoop et al, 2003;DiCarlo et al, 2003;Swaddiwudhipong et al, 2005), which all aim at overcoming the non-uniqueness of the reverse analysis of material properties from a single indentation test (Futakawa et al, 2001;Cheng and Cheng, 2004).…”
Section: Dual Indentation Approachmentioning
confidence: 99%
“…Therefore, the mechanical properties of these specimens cannot be uniquely determined by using only one sharp indenter. In turn, the indentation community now believes that the dual (or plural) sharp indentation analyses would yield unique solutions, since it is not likely that a set of special materials would again yield the same indentation characteristics when a different sharp indenter is used (Futakawa et al, 2001;Bucaille et al, 2003;Capehart and Cheng, 2003;Chollacoop et al, 2003;DiCarlo et al, 2003;Cao and Lu, 2004a;Cheng and Cheng, 2004;Tho et al, 2004;Alkorta et al, 2005;Swaddiwudhiponga et al, 2005;Cao and Huber, 2006). From dimensional analysis, the number of the indenters with different apex angles can be equal to the number of additional unknown material constants, so as to determine them uniquely (Futakawa et al, 2001;Cheng and Cheng, 2004;Swaddiwudhiponga et al, 2005).…”
Section: Introductionmentioning
confidence: 99%